The Effect of Digital Marketing on Organizational Performance Through Intellectual Capital and Perceived Quality in Micro, Small and Medium Enterprises - Nurul Islami, Novita; Wahyuni, Sri; Tiara, Tiara (LPPM Universitas Terbuka, 2020)
Digital marketing is one of marketing media taken as an opportunity to expand the marketing area with the help of digital technology for Small, Micro and Medium Enterprises (MSMEs) which have a limited average background in terms of capital. These issues encourage the researchers to conduct the study entitled the effect of digital marketing on organizational performance through intellectual capital and perceived quality in Micro, Small and Medium Enterprises (MSMEs) in East Java. This is explanatory research that uses a survey method by distributing questionnaires through a quantitative approach and using PLS as data analysis. Findings. The results showed that there are weaknesses of MSMEs in Perceived Quality, so it is needed training especifically related to digital marketing which involves intellectual capital and perceived quality to improve organizational performance. MSME as one of the informal sectors that plays a role in supporting the community's economy in order to survive and develop.